Pengaruh teat dipping menggunakan dekok daun kersen (Muntingia calabura L.) terhadap tingkat kejadian mastitis - Indra Kurniawan; S. Sarwiyono; Puguh Surjowardojo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
ABSTRACT: The study was carried out in Sidomulyo Village, Jabung, Malang Regen-cy from April 6th to May 6th, 2013. The objective of the study was to evaluate the influ-ence of Kersen leaf (Muntingia calabura L) extract to reduce mastitis incidents. The materials used in this study were 15 Friesian Holstein crossbreed lactating dairy cows, chemical antiseptic, and Kersen leaf extract. The study used experiment Randomized Block Design with 3 treatments and 5 replications. The result shows that Kersen leaf extract was significantly (p>0.05) able to reduce mastitis incidents particularly 20% of Kersen leaf extract composition. The study suggests that Kersen leaf extract can be used as an effective substance in dipping solution for dairy cows Mastitis control program.Keywords: Kersen leaf extract, mastitis, teat dipping, dairy cows